2020
DOI: 10.1016/j.socscimed.2020.112913
|View full text |Cite
|
Sign up to set email alerts
|

Diverging ideas of health? Comparing the basis of health ratings across gender, age, and country

Abstract: Background Self-rated health (SRH) is arguably the most widely used generic health measurement in survey research. However, SRH remains a black box for researchers. In our paper, we want to gain a better understanding of SRH by identifying its determinants, quantifying the contribution of different health domains to explain SRH, and by exploring the moderating role of gender, age groups, and the country of residence. Method Using data from 61,365 participants of the fif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 79 publications
5
37
0
Order By: Relevance
“…Spearman correlations and linear regression analysis were performed, determining the direct relationships and relative contributions of the health determinants as well as the socioeconomic and demographic determinants to perceived TGH. Linear regression is a justi ed way to analyse these relationships (32). T-tests and one-way ANOVA were used to test for statistical differences between the SES groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spearman correlations and linear regression analysis were performed, determining the direct relationships and relative contributions of the health determinants as well as the socioeconomic and demographic determinants to perceived TGH. Linear regression is a justi ed way to analyse these relationships (32). T-tests and one-way ANOVA were used to test for statistical differences between the SES groups.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were asked to assess their total perceived health and their perceived health on each of the six dimensions of the positive health concept after scoring the 32 items of the positive health scale from 1 (poor) to 5 (excellent). In this way all respondents evaluated their health on the same topics, avoiding different interpretations of health (32).…”
Section: Research Population and Data Collectionmentioning
confidence: 99%
“…Although the most significant determinants of an individual's poor self-rated health are physical functioning (GALI) and presence and knowledge about chronic morbidity, self-rated health reflects essential dimensions that the other two measures are less likely to include. In particular, this includes mental health and bodily pain (Au and Johnston, 2014;Hardy et al, 2014;Jylhä et al, 1998;Lazarevič, 2019;Lazarevič and Brandt, 2020;Saito et al, 2014;Simon et al, 2005;Singh-Manoux et al, 2006). Likewise, the observed that the effects of decreased health on well-being depends on the specification of the health dimension applied in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, and for comparability with previous studies, we also considered marriage effects on self-rated health. Self-rated health is frequently used in large-scale studies because it is highly predictive of mortality risks (Schnittker & Bacak, 2014), correlates with disease incidence (Wu et al, 2013) and domain-specific dimensions of health (such as functioning, diseases, and pain; Lazarevič, 2018, Lazarevič & Brandt, 2020. Qualitative research suggested that it reflects aspects of both physical and mental health (Simon et al, 2005).…”
Section: Datamentioning
confidence: 99%